SITUS KRATON PLERED SEBAGAI MEDIA PEMBELAJARAN REKONSTRUKSI SEJARAH - Febta Pratama (Indonesian Journal of Social Science Education (IJSSE), 2019)
Abstract: The Palace Site Plered as a Learning Media of Historical Reconstruction. The purpose of research on the Palace Site Plered during Islamic Mataram was to see how big the potential and the prospective site of the Palace as a learning Medium Plered Reconstruction History either to students, a student of history, as well as lovers of history. This research uses qualitative deskriftif method with this type of research is historical. As for the method of this research consists of the stages of data collection, data analysis, and then the last stage of verification or conclusion. In the third stage of the four-stage research history. The results showed that the Palace historical site Plered beneficial to provide insight into the history of the Sultanate of Mataram Islam and has potential as a medium of instruction in developing the learning model reconstruction of history. The Palace site is useful as a productive activity of Plered as preparation of scientific papers, final project, the creation of media, and natural history education, laboratory for students, students of history and public history lovers.